Trinidad and Tobago : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation highlights that the economy of Trinidad and Tobago is turning the corner, and growth is expected to resume in 2012 after an extended slowdown lasting three years. Real economic activity is expected to increase by 1.7 percent in 2012 as the nonenergy sector picks up momentum with the acceleration of government investment. Executive Directors have welcomed the signs of economic recovery following a prolonged slowdown, and commended the authorities for implementing supportive policies, aided by ample buffers, which had helped maintain stability.